The Efficiency of Islamic Rural Banks (BPRS) in South Sulawesi - Nur Khatimah; Titis Miranti (I-Finance Journal, 2022)
This study aims to determine the efficiency level of Islamic Rural Banks (BPRS) in South Sulawesi and determine what influences it. The study population is the BPRS in South Sulawesi registered with the Financial Services Authority (OJK). The study sample used the purposive sampling method and obtained 7 BPRS in South Sulawesi. The data source comes from the quarterly financial reports of the BPRS. The analysis technique is two stages – data envelopment analysis (DEA). The results of the first stage, using DEA, found that the average efficiency of the BPRS Indo Timur, Dana Moneter, Surya Sejati, Investama Mega Bakti and Harta Insan Karimah Makassar was 1, Niaga Madani was 0.829, while Gowata was 0.993. The second stage, using Tobit regression, found that fixed assets, operating costs, and operating income showed significant results in the alpha value. Meanwhile, total savings, profit-sharing financing, and productive assets showed no significant results on the alpha value. The first stage concludes that the BPRS in South Sulawesi is not included in the efficient level. In the second stage, the variables of fixed assets, operating costs, and operating income partially affect the efficiency value of the BPRS.